Do school-to-work programs help the forgotten half? - David Neumark; Donna Rothstein (Institute for the Study of Labor (IZA), 2005)
This paper tests whether school-to-work (STW) programs are particularly beneficial for those less likely to go to college in their absence often termed the forgotten half in the STW literature. The empirical analysis is based on the NLSY97, which allows us to study six types of STW programs, including job shadowing, mentoring, coop, school enterprises, tech prep, and internships/apprenticeships. For men there is quite a bit of evidence that STW program participation is particularly advantageous for those in the forgotten half. For these men, specifically, mentoring and coop programs increase post-secondary education, and coop, school enterprise, and internship/apprenticeship programs boost employment and decrease idleness after leaving high school. There is less evidence that STW programs are particularly beneficial for women in the forgotten half, although internship/apprenticeship programs do lead to positive earnings effects concentrated among these women.
Keywords: I28; J15; J24; 330; Jugendliche Arbeitskräfte; Arbeitsmarktpolitik; USA